Jejak Langkah Multikulturalisme di Pura Pabean Pulaki Singaraja Bali - I Gusti Ngurah Sudiana; I Nengah Alit Nuriawan (Universitas Udayana, 2022)
This article analyzes the footsteps of multiculturalism in North Bali by using as the object of analysis the Pura Pabean (Custom Temple) which is upheld by Hindus and Confucians. The analysis focuses on four things, the first, namely: describing the history of the founding of the Pabean Temple; the second regarding the form and function of the traces of multiculturalism in the Pabean Temple; the third the trace of multiculturalism in Pabean temple; and the fourth being the contribution of Pabean Temple in building multiculturalism in Bali. This study is a qualitative study whose data were collected using observation, interview, and literature review techniques. The data were analyzed using the theory of multiculturalism. The results of the analysis show that the Pabean Temple, which is believed to have been established in the 15th century, is historical evidence of multiculturalism that has been going on for a long time in Bali. This is also with the existence of two sacred buildings side by side in one temple area that is upheld, even though they are residents with different beliefs, namely Hinduism and Kong Hu Chu. This article provides a new contribution to the history and dynamics of multiculturalism that is maintained in Bali, especially from a temple called Pura Pabean in North Bali.